Applying a physiologic partograph to Consortium on Safe Labor data to identify opportunities for safely decreasing cesarean births among nulliparous women. Issue 4 (30th May 2018) - Neal, Jeremy L.; Lowe, Nancy K.; Caughey, Aaron B.; Bennett, Kelly A.; Tilden, Ellen L.; Carlson, Nicole S.; Phillippi, Julia C.; Dietrich, Mary S.
Abstract: Background: The timing of hospital admission for women with spontaneous labor onset and the criteria used to assess active labor progress and diagnose labor dystocia may significantly influence women's risk for primary cesarean birth. Our aims were to assess associations of labor status at admission (i.e., preactive or active) and active labor progress (i.e., dystocic or physiologic) with oxytocin augmentation, cesarean birth, and adverse neonatal outcome rates. Methods: A sample of low‐risk, nulliparous women admitted to hospitals for spontaneous labor onset was extracted from the Consortium on Safe Labor (n = 27 077). Binomial logistic regression was used to assess associations between labor classifications and outcomes. Results: At admission, 68.0% of women were in preactive labor and 32.0% were in active labor. Cesarean rates for these groups were 18.0% and 7.2%, respectively (adjusted odds ratio [AOR] 2.69; 95% CI 2.45‐2.96). Oxytocin augmentation and adverse neonatal outcomes were more likely for women admitted in preactive labor. Among women admitted in active labor, 9.3% experienced labor dystocia and 90.7% progressed physiologically. Cesarean rates for these groups were 20.4% and 5.9%, respectively (AOR 3.02; 95% CI 2.45‐3.73). Nearly half of the cesareans performed for dystocia among women admitted in active labor occurred when cervical dilation was physiologic. Oxytocin augmentation and adverse neonatal outcomes were more likely when active labor was dystocic. Conclusions: Adoption of evidence‐based, standardized approaches for diagnosing active labor onset, assessing labor progress, and diagnosing dystocia may safely decrease oxytocin augmentation and cesarean birth rates in the United States.